2000
DOI: 10.1143/jjap.39.5788
|View full text |Cite
|
Sign up to set email alerts
|

Two Levels of Ni/n-GaAs Schottky Barrier Heights Formed on a Wafer by Controlling pH of Pretreatment Chemicals: Effect of Oxygen Adsorption

Abstract: Schottky barrier heights of Ni/n-GaAs junctions were controlled by changing the pH of pretreatment chemicals. An effective barrier height of 0.8 eV was obtained by treatment with dilute HCl liquid (pH = l), and 0.6 eV by treatment with dilute NH4OH liquid (pH = 13). Surface analysis by an x-ray photoelectron spectroscopy indicated the existence of about twice the density of oxygen at the surface of the HCl-treated wafer as compared with that pretreated by the NH4OH liquid. The former shows nearly linear C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Figure 9 shows the transconductance versus gate voltage curves of the samples. 14) The MISFETs show a higher peak transconductance and the pinch-off voltages shifted toward the positive direction, reproducing the nitridation effects demonstrated by the HW plasma system. 12) Sample No.…”
Section: Characteristicsmentioning
confidence: 57%
See 1 more Smart Citation
“…Figure 9 shows the transconductance versus gate voltage curves of the samples. 14) The MISFETs show a higher peak transconductance and the pinch-off voltages shifted toward the positive direction, reproducing the nitridation effects demonstrated by the HW plasma system. 12) Sample No.…”
Section: Characteristicsmentioning
confidence: 57%
“…In the mean time, wafer No. 1 was processed with HCl 14) and kept in air. Therefore, it may have a-few-nm thick native oxide.…”
Section: Fabrication Of Fetsmentioning
confidence: 99%
“…Our previous characterization of a GaAs surface by X-ray photoelectron spectroscopy (XPS, back pressure 10 À8 Torr) demonstrated the existence of O even after Arion etching. 6) These findings suggest that a high vacuum provides a weak oxidation condition and a GaAs surface 17) with a (2Â) structure, observed using a high-vacuum scanning tunneling microscope, is possibly generated by a Ga 2 O Structure, as shown in Fig. 15(a).…”
Section: Degrade-then-improvementioning
confidence: 75%
“…In addition to kinetic energy, incorporation of oxygen has also been postulated as a cause of ''interface degradation'', because oxygen is widely known to be a generator of deep levels. However, Houng et al reported a correlation between the concentration of the growth solution and the resultant performance of electrochemically deposited SiO 2 films on GaAs, 5) and Tsuzuku et al demonstrated pH-dependent Schottky barrier heights of Ni/n-GaAs junctions, 6) and showed that oxygen does not always degrade the interface. Moreover, the oxidation of GaAs 7) and InAlAs 8) by an ultraviolet and ozone (UV and ozone) process clearly indicated that oxidation does not result in monotonically increasing damage to the crystal but ''degrade-then-recover'' phenomena occur depending on progress of the oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Energy (eV) processed Schottky and MOS devices suggested that such crystal degradation possibly occurs even without high kinetic energy or high temperature. 14,15) Thus, another mechanism of defect/disorder generation must be considered, in addition to the above-mentioned ones. It is widely known in the technical field of hetero epitaxy that a large lattice mismatch generates such defects and disorder when the thickness exceeds a critical value, because the mismatch distorts the tetrahedral symmetry of the mother crystal (or epitaxial layer) and originates a strong mechanical stress at the interface.…”
Section: Ge 4s Ge 4pmentioning
confidence: 99%